Δ9-Tetrahydrocannabinol During Adolescence Attenuates Disruption of Dopamine Function Induced in Rats by Maternal Immune Activation - Lecca, Salvatore; Luchicchi, Antonio; Scherma, Maria; Fadda, Paola; Muntoni, Anna Lisa; Pistis, Marco (Frontiers in Behavioral Neuroscience, 2019)
The combination of prenatal, such as maternal infections, and postnatal environmental insults (e.g. adolescent drug abuse) increases risks for psychosis, as predicted by the two-hit hypothesis of schizophrenia. Cannabis abuse during adolescence is widespread and is associated with increased risk of psychoses later in life. Here, we hypothesized that adolescent Δ9-tetrahydrocannabinol (THC) worsens the impact of prenatal maternal immune activation (MIA) on ventral tegmental area (VTA) dopamine cells in rat offspring. Additionally, since substance abuse disorder is particularly prevalent among schizophrenia patients, we also tested how VTA dopamine neurons in MIA offspring respond to acute nicotine and cocaine administration. We used a model of neurodevelopmental disruption based on prenatal administration of the polyriboinosinic-polyribocytidilic acid [poly(I:C)] in rats, which activates the maternal immune system by mimicking a viral infection and induces behavioral abnormalities and disruption of dopamine transmission relevant to psychiatric disorders in the offspring. Male offspring were administered THC (or vehicle) during adolescence (PND 45-55). Once adult (PND 70-90), we recorded spontaneous activity of dopamine neurons in the VTA and their responses to nicotine and cocaine. MIA male offspring displayed reduced number, firing rate and altered activity pattern of VTA dopamine cells. Adolescent THC attenuated several MIA-induced effects. Both prenatal [poly(I:C)] and postnatal (THC) treatments affected the response to nicotine but not to cocaine. Contrary to our expectations, adolescent THC did not worsen MIA-induced deficits. Results indicate that the impact of cannabinoids in psychosis models is complex.